Portraits de Résistantes (1847-1875) : la femme face au système patriarcal dans quelques romans victoriens - Jacqueline Fromonot (Cahiers Victoriens et Edouardiens)
The analysis bears on the literary representations of women’s resistance to patriarchal figures, drawing from a wide-ranging corpus. Passive resistance is depicted—and often denounced—in Thackeray and Eliot as a pattern of behaviour imposed by a world that expects women to resist male desire in courtship and to master their own impulses in society, in the name of decorum and decency. Nonetheless, this skilful suppression of feeling paradoxically proves at times an aid to secret resistance, thanks to which women only seem to obey. More active ways of resisting are based on lying and deception, a mise en abyme of literary creation itself—a signature in Thackeray and Meredith. However, the freedom women obtain from such dissent is doomed, as resistance remains covert and does not result in overt claims likely to challenge the patriarchal system. Yet, some novelists stage dramatic forms of frontal attack and resistance, in which women choose heroic postures by emphatically rejecting the male-dominated world, like Dickens’s Estella in Great Expectations. Greatly influenced by the sensational genre, Trollope, on his part, creates a wilful character resisting her father in The Way We Live Now. However, the eponymous heroine of the earliest novel of the corpus, Jane Eyre, proves strikingly ahead of her time in her systematic defiant refusal of all forms of patriarchal domination—and her overall success in doing so.